Intraoperative Consultation of Sino-Nasal Lesions: A Decade Experience at Tertiary Care Hospital - RAVINDRA, SNEHA; JAVALGI, ANITA P; ATHANIKAR, VIDISHA (International Journal of Innovative Research in Medical Science, 2023)
Background: Sino-nasal lesions present similar to each other ranging from congenital, infectious, inflammatory, and traumatic to neoplastic causes, which need histopathological confirmation. Lesions like fungal sinusitis represent a fulminant, potentially fatal, disease process in immunocompromised patients. The diagnosis rests on high index of clinical suspicion with diagnostic and therapeutic implications of intraoperative consultation. Present study aimed at evaluation of sensitivity, specificity and diagnostic accuracy of intraoperative consultation in Sino-nasal lesions. Design: Present study is 10year observational cross-sectional study (October 2011 to October 2021). A total of 203 Sino-nasal lesions that were received for intraoperative consultation at histopathology laboratory were included. Frozen slides and confirmed histopathology slides of these cases were reviewed and statistical analysis done. Results: Total 203 cases were reviewed. The cases were categorised into non neoplastic, benign and malignant lesions. Fungal sinusitis (mucormycosis> aspergillosis > candidiasis) was commonest in non-neoplastic, inverted papilloma was commonest in benign lesions and adenocarcinoma was commonest in malignant lesions. Male predominance was seen in all 3 categories. Predominant age group affected was 41-60 years. The sensitivity, specificity, positive predictive value, and negative predictive value of non-neoplastic, benign and malignant lesions of frozen section were 93%, 75%, 98.80%, and 64.86%; 100%, 100%,100%, and 100%; and 100%, 98.90%, 100% and 85.70%, respectively. Conclusion: Present study emphasises that frozen studies are highly sensitive in the diagnosis of Sino-nasal lesions. Intra-operative diagnosis of fungal infections thereby facilitates immediate targeted treatment strategies for optimal outcomes.